Research of EU Educational Systems in Pedagogical Theory: Compulsory and Professional Education - Krystopchuk, Tetyana (Pedagogical Discourse, 2012)
The article analyzes the development of educational systems of the European Union in the pedagogical literature. The structure of compulsory education and professional training problems, which are in the spotlight of EU member states, are defined in the article.